Along the Rio Grande - Peterson, Tracie (Love on the Santa Fe, 2022)
"When bankruptcy forces widow Susanna Jenkins to follow her family to New Mexico, what they see as a failure she sees as a fresh start. Owen Turner is immediately attracted to Susanna, but he's afraid of opening up his heart again, especially as painful memories are stirred up. But if Owen can't face the past, he'll miss out on his greatest chance at love"--